BACTERIAL CONSORTIUM POTENCY FOR BIOREMEDIATION OF SEWAGE AT PESANGGARAN SLAUGHTTERHOUSE BALI - Putra, Gusti Ngurah Wisnanda; Kawuri, Retno; Subagio, Job Nico (SIMBIOSIS, 2022)
Slaughterhouses produce solid waste and liquid waste. The liquid waste consists of urine, blood, fat, and carcass washing water which causes pollution to the environment if not treated in a good way. This study aims to determine the potential of a consortium of bacteria (Bacillus sp., Klebsiella sp.) in remediating the abattoir wastewater. This research was conducted from January to April 2021 at the Microbiology Laboratory of the Biology Study Program, Faculty of Mathematics and Natural Sciences, Udayana University, and the Analytical Laboratory of Udayana University, using the Sequence Batch Reactor (SBR) method, with the varying treatment of a consortium of bacteria concentration   i.e 0 (as control), 10, 20, 30, 40, and 50 mL in 2 liters of liquid waste. Parameters observed were changes in physical parameters, BOD5, Total Plate Number (ALT), and nitrite and nitrate content of waste samples. The results of this study showed that treatment 5 is giving a bacterial consortium dose of 50 mL/2 liters of wastewater was the most effective dose with a BOD5 value of 0.82 g/L, clear yellow without odor, TDS Final Value 539.6 mg/L, and the number of bacteria 9.54 x 10 10 and a decrease in nitrite and nitrate by -0.001 and 1.743 mg/L